Reproductive and tissue plasticity in Arca noae (Bivalvia: Arcidae). Issue 1 (1st January 2017) - Ghribi, F.; Bello, G.; Zupa, R.; Passantino, L.; Santamaria, N.; El Cafsi, M.; Corriero, A.
Abstract: The reproductive strategy of an unexploited population of Arca noae from the salt-water Bizerte Lagoon (Tunisia, western Mediterranean), including its tissue plasticity, was studied. In total 309 individuals, collected monthly from October 2013 to September 2014, were examined; 142 were females, 42 were males and five were hermaphrodites. They were used in histological and immunohistochemical (stem marker: Pou5f1; proliferation marker: proliferating cell nuclear antigen (PCNA)) analyses of gonads and adjacent tissues (NÂ =Â 189) as well as to compute the monthly condition index (NÂ =Â 120). Water salinity, temperature and chlorophyll a concentration were recorded. Ripe ovaries were observed in two discrete periods, Octoberâ€"November and Aprilâ€"August. Both gonad ripenings were followed by spawning periods, Novemberâ€"April and Julyâ€"September. The mature oocyte density showed that the first spawning period was less vigorous than the second one. These data also indicated that A. noae is a multiple spawner. Five cases of protandric hermaphroditism occurred from December to April. Gonad tissue was strictly associated and intermingled with the digestive gland and mantle muscle fibres. Seasonal variations were observed in the relative proportions of digestive gland and gonads: the former predominated when the latter regressed (March) and vice versa (peak in June). Seasonal transitions from germinal to somatic tissue and vice versa were hypothesised to occur through transdifferentiation mechanisms based on the activity of stem and proliferating cells. The condition index roughly increased along with gonad ripening and decreased during the spawning periods, although it did not run parallel to gonad evolution, because it also depended on chlorophyll a concentration, a proxy for phytoplankton density. The condition index was significantly correlated, by multiple regression, to both mature oocyte density and chlorophyll a concentration. Arca noae appears to have evolved a flexible reproductive strategy that makes it capable of exploiting diverse environmental conditions, which also involves tissue transdifferentiation.